2019
DOI: 10.4103/ijn.ijn_78_18
|View full text |Cite
|
Sign up to set email alerts
|

Volume assessment in hemodialysis: A comparison of present methods in clinical practice with sonographic lung comets

Abstract: Dry weight assessment in dialysis patients remains a challenging endeavor owing to the limitations of the available methods for volume assessment. Lung ultrasound is emerging as an invaluable tool to assist in the appropriate assessment and assignment of dry weight. The objectives of this study are (1) to determine the reliability of clinical signs and symptoms for volume assessment, (2) to compare lung ultrasound with High Resolution Computed Tomography (HRCT) chest-A noninvasive gold standard tool for detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…11 Lung congestion, as determined by the count of sonographic B-lines, can be classified into categories of severity: mild (<14 comets), moderate (14-30 comets), or severe (>30 comets). 6,22,48 In our review, seven studies indicated mild congestion, one showed moderate congestion, and three demonstrated severe lung congestion pre-hemodialysis. It's noteworthy that traditional clinical signs, such as lower limb edema and auscultatory crackles, show lower sensitivity and accuracy.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…11 Lung congestion, as determined by the count of sonographic B-lines, can be classified into categories of severity: mild (<14 comets), moderate (14-30 comets), or severe (>30 comets). 6,22,48 In our review, seven studies indicated mild congestion, one showed moderate congestion, and three demonstrated severe lung congestion pre-hemodialysis. It's noteworthy that traditional clinical signs, such as lower limb edema and auscultatory crackles, show lower sensitivity and accuracy.…”
Section: Discussionmentioning
confidence: 80%
“…Sonographic B‐lines exceeding five serve as an early indicator of pulmonary congestion, frequently preceding the onset of apparent pulmonary edema by approximately 2 weeks 11 . Lung congestion, as determined by the count of sonographic B‐lines, can be classified into categories of severity: mild (<14 comets), moderate (14–30 comets), or severe (>30 comets) 6,22,48 . In our review, seven studies indicated mild congestion, one showed moderate congestion, and three demonstrated severe lung congestion pre‐hemodialysis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…From the 46 articles selected for full-text review, we excluded another 20 articles: 5 review articles (all studies mentioned in these manuscripts had already been included in our review), 1 editorial, 1 meta-analysis, 6 articles that did not study the exposure of interest, 4 articles that did not present the outcome(s) of interest, 2 articles were subanalyses of an included randomized controlled study. A total of 28 studies were included in our systematic review: 25 observational studies, 4 , 26 - 49 and 3 RCTs as shown in Figure 1 . 18 , 19 , 50 The randomized controlled studies did not address the same endpoints as the observational studies and are separately presented in a different section of the results.…”
Section: Resultsmentioning
confidence: 99%